Evaluating effectiveness of risk identification and management using organisational models - Bhuiyan, M.; Rana, S.; Krishna, Aneesh (IEEE, 2011)
In this paper firstly we discuss an approach for supporting risk identification with the use of higher-level organizational models. We provide some intuitive metrics for extracting measures of actor criticality and vulnerability from organizational models. This helps direct risk management to areas of critical importance within organization models. Secondly, we provide details of an experiment that weconducted to evaluate our methodology. We believe our novel approach, will provide added benefits when used with other approaches to risk management during business process management, that do not reference the greater organizational context during risk assessment.